The Neural and Psychological Processes of Peer-Influenced Online Donation Decision: An Event-Related Potential Study - Ye, Yuchen; Jiang, Pengtao; Zhang, Wuke (Frontiers in Psychology, 2022)
With the rapid development of information and communication technology (ICT), social media-based donation platforms emerged.1 These platforms innovatively demonstrate peer information (e.g., number of donated peers) on the donation page, which inevitably brings the peer influence into donors’ donation decision process. However, how the peer influence will affect the psychological process of donation decisions are remained unknown. This study used the number of donated peers to examine the effects of peer influence on donors’ donation decisions and extracted event-related potential (ERP) from electroencephalographic data to explore the underlying psychological process. The behavioral results indicated that the number of donated peers positively influenced donors’ willingness to donate. The ERP results suggested that a larger number of donated peers might indicate a higher level of conformity and greater perceived emotional rewards, as a larger P2 amplitude was observed. Following the early processing of emotional stimuli, cognitive detection of decisional risk took place, and the donors reckoned a smaller number of donated peers as a high potential risk, which was reflected by a larger N2 amplitude. In the later stage, the larger number of donated peers, which represented a higher magnitude of prospective emotional rewards, led to a higher incentive to donate, and reflected in a larger amplitude of P3. Additionally, implications and future directions were discussed.